2004
DOI: 10.1007/bf02725643
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of clinical presentations of vein of Galen aneurysm

Abstract: Aneurysm of the vein of Galen is a rare intracranial vascular malformation. It is known to have diverse manifestations and varying severity. Four cases with different modes of presentation and outcome are reported. A mortality of 50 per cent was encountered. Among the survivors, one had neurologic sequelae whereas the other had attained age-appropriate developmental milestones. The former was a rare case of spontaneous thrombosis of the aneurysm while the latter was a boy who underwent therapeutic embolization. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
0
17
0
5
Order By: Relevance
“…Au niveau cardiaque, le shunt vasculaire à débit élevé est responsable d'une défaillance cardiaque dont la gravité est corrélée à l'importance du shunt [2,8,12]. Quelques malformations cardiaques peuvent s'associer à l'AVG à savoir la coarctation aortique, le sinus venosus et la communication interauriculaire [5]. In utero, les conséquences de ce shunt sont plus atténuées du fait que les résistances placentaires basses protègent le foetus par un phénomène de compétition avec les résistances basses de la fistule [9,10].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Au niveau cardiaque, le shunt vasculaire à débit élevé est responsable d'une défaillance cardiaque dont la gravité est corrélée à l'importance du shunt [2,8,12]. Quelques malformations cardiaques peuvent s'associer à l'AVG à savoir la coarctation aortique, le sinus venosus et la communication interauriculaire [5]. In utero, les conséquences de ce shunt sont plus atténuées du fait que les résistances placentaires basses protègent le foetus par un phénomène de compétition avec les résistances basses de la fistule [9,10].…”
Section: Discussionunclassified
“…Elle représente moins de 1 % des malformations artérioveineuses cérébrales congénitales [1][2][3][4]. Elle se révèle à l'âge néonatal dans 40 à 50 % des cas [2,5], le plus souvent par un tableau d'insuffisance cardiaque. La malformation est rarement découverte in utero.…”
unclassified
“…In adults, this pathology has been described by some authors 3,6,7,[14][15][16][17][18][19][20] . Because of its rarity in adults, and despite what is known from these studies, there is still insufficient information about this disease during adult age 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The indications of these treatments are based on case-specific clinical manifestations 9 . Sasidharan et al 20 , suggested conservative conduct and patient monitoring for those with severe heart failure. The absence of blood flow at the deep cerebral venous system due to malformation thrombosis, absence of signs or symptoms of intracranial hypertension, and pharmacological control of seizures led us to conservative treatment of the patient presented here.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Mortality rates are reported between 50% and 100% for neonates. 4 Survivors often have severe mental and neurologic limitations.…”
Section: Answer To Diagnostic Challenge (From Page 43) a Hole In The mentioning
confidence: 99%